2020
DOI: 10.1155/2020/2728949
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice (KAP) of Radiographic Protection by Dental Undergraduate and Endodontic Postgraduate Students, General Practitioners, and Endodontists

Abstract: The aim of this study is to evaluate the knowledge, attitude, and perception of radiation hazard and preventive measures among dental undergraduate students, general practitioners, endodontic postgraduate students, and endodontists in Saudi Arabia. Multiple choice questions questionnaires were distributed among undergraduate and endodontic postgraduate dental students, general practitioners, and endodontists in the colleges of dentistry in Saudi Arabia, government hospitals, and private clinics. The questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
1
8
0
4
Order By: Relevance
“…Whereas Srivastava et al ., 83.3%, Rathi Rela reported 56%, Swapna et al ., reported 59%, Almohaimede et al ., reported 60.8%, and Basheer et al ., reported 63.5% of their participants were knew that dental X-rays are harmful to health. [ 15 17 18 19 20 ] Our results show that the range of knowledge better than the previous studies. Even though the dental radiation dose is minimal, its better to avoid taking radiographs in the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Whereas Srivastava et al ., 83.3%, Rathi Rela reported 56%, Swapna et al ., reported 59%, Almohaimede et al ., reported 60.8%, and Basheer et al ., reported 63.5% of their participants were knew that dental X-rays are harmful to health. [ 15 17 18 19 20 ] Our results show that the range of knowledge better than the previous studies. Even though the dental radiation dose is minimal, its better to avoid taking radiographs in the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 38%
“…Previously conducted studies by Srivastava et al ., 59.8%, Rathi Rela 64%, Swapna et al ., 58%, and Bahseer et al ., 63.2%, of their revealed that their participants were aware of consideration to taken during patient's trimester of pregnancy. [ 15 17 18 20 ] According to Srivastava et al ., 59.8% of his study participants had proper knowledge annual recommended occupational radiation dose limit for operators. [ 15 ] In our study revealed that approximately 81% of the participants were having awareness about it.…”
Section: Discussionmentioning
confidence: 99%
“…Persepsi tersebut bahkan lebih rendah dibandingkan dengan persepsi dokter gigi terhadap penggunaan celemek timbal yang ditunjukkan dengan persentase penggunaan celemek timbal pada pasien lebih tinggi dibandingkan persentase penggunaan pelindung tiroid pada pasien. 3,36 Selain dipengaruhi oleh anggapan yang keliru di kalangan dokter gigi mengenai pentingnya perlindungan organ tiroid, rendahnya persepsi dokter gigi terhadap penggunaan pelindung tiroid dapat terjadi karena ketidakpatuhan dalam menggunakan pelindung tiroid. Banyak alasan yang menyebabkan ketidakpatuhan tersebut, di antaranya adalah terbatasnya jumlah pelindung tiroid, ukuran pelindung tiroid yang cukup besar sehingga rawan mengalami kerusakan jika tidak digunakan secara hati-hati, ketidaknyamanan pasien karena pelindung berkontak langsung dengan kulit, serta desain pelindung tiroid yang tidak ergonomis sehingga susah dipasang di leher pasien.…”
Section: Persepsi Dokter Gigi Terhadap Penggunaan Pelindung Tiroidunclassified
“…Risiko timbulnya efek tersebut akan semakin besar jika prosedur radiografi semakin sering dilakukan pada pasien. 3,4 Tiroid adalah organ pada leher yang sangat esensial karena berfungsi menghasilkan hormon yang berperan penting dalam menjaga keseimbangan proses metabolisme tubuh manusia. Terganggunya organ ini memengaruhi kualitas hidup individu.…”
unclassified
“…The ability of the ionizing radiation to penetrate the soft tissue and reflecting an image which cannot be seen on a sensor by naked human eye gives it great importance in multiple branches of dentistry. The usage of radiographs varies from diagnosing minor carious lesions to periapical lesions of odontogenic and nonodontogenic origin [2] and for evaluation of cases for a better treatment planning [3]. Ionizing radiation, nevertheless, could be biologically damaging to the living tissues [4].…”
Section: Introductionmentioning
confidence: 99%